Análise de cenários para o gerenciamento de resíduos sólidos domésticos recicláveis no horizonte do plano de gerenciamento da Bacia Hidrográfica do Rio dos Sinos - Goetze, Camila (Universidade do Vale do Rio dos Sinos, 2009)
The dissertation was divided in three major parts: (i) bibliographic review; (ii) domestic recyclable solid waste management current situation diagnosis; (iii) prognosis for the next 10 and 20 years. From the identification of domestic recyclable solid waste management quality indicators was possible to start the current situation diagnosis in the cities of SRHB sample components, using the help of ArcMap software and bibliographic review. Wich indicated the growing indices hallowing to generate the prognosis for the next 10 and 20 years. The prognosis analysis indicated the reasons why some cities will have a better or worse future scenario, helping the environmental managers in the strategic actions planning for the domestic recyclable solid waste management. Among them, the present study could highlight the support to collector's cooperative, through financial and educacional incentives to improving processes; reform of selective collect systems; and necessity of investment in awareness programs and education.In short, this work?s relevance consists in developing an analysis method using the ArcGIS software, which can be used in the development of Plano Sinos (Sinos Plan) studies. From the georeferenced data base creation, any change in current panorama could be easily imputed e generated a new analysis, warning the managers to take preventives actions.
Keywords: Resíduo sólido urbano; Bacia hidrográfica do Rio dos Sinos; Gerenciamento ambiental; ACCNPQ::Engenharias::Engenharia Civil